Analysis on Malaysians’ consumers acceptance towards organic banana in Malaysia / Muhammad Naim Shaharudin and Nor Amalina Ismail - Shaharudin, Muhammad Naim; Ismail, Nor Amalina (Faculty of Plantation and Agrotechnology, 2018)
Organic banana is one of the nutritional foods and it is good for health. Eating organic banana may-add additional health benefits as compare to eating non-organic banana. Organic banana contain less synthetic fertilizer, artificial colouring, flavouring, sweeteners and preservations, some of it may be harm fill for human body. The study was conducted to identify the determinants or factor that influenced the consumers acceptance towards organic banana in Malaysia. The survey method was used for data collection. The questionnaires were distributed to 52 respondents that consists of consumer in Malaysia. The results were interpreted by factor analysis by using Statistical Package for Science Computer Software (SPSS) version 23. There were three independent variables for the studies which were price, knowledge and environmental concern. The result from the factor analysis based on the KMO’s value showed that 0.582 which was moderate. The KMO’s value greater than 0.5 was considered acceptable. From the total variance explained, price factor was dominant attribute represented by four factors which were eigenvalues more than 1. The factors were willing to pay extra (4.476). affordable price (2.388). interested to buy (1.776) and price suitable with quality (1.401). It showed that 71.73% of the variance would be explained by the factors. It showed that 71.73% of the variance would be explained by the factors. Thus, it can be concluded that there was a strong positive relationship between price and Malaysian consumer’s acceptance towards organic banana and it show that price was most dominant factor on Malaysian consumer’s acceptance towards organic banana.